Pelatihan Ketrampilan Kader dalam Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Darul Imarah Kabupaten Aceh Besar - Nurhayati, Nurhayati; Hanum, Faridah (LP2M Institut Agama Islam Nazhatut Thullab Sampang, Indonesia, 2024)
Breastfed babies are specially protected from digestive system diseases such as diarrhea, dysentery, gastro enteritis and ulceracy colitis. This is because the immune substances in breast milk provide direct protection against disease attacks. The purpose of the program is to empower the community and can produce changes in knowledge, attitudes, and behaviors of the target group and the community. Community Service activities are carried out in the form of Cadre Training with lecture, demonstration, and Role Play methods. The results of knowledge measurement were in the good category during the pretest which was 67% and increased at the time of postest which was 93%. The results of observations of counseling actions from 15 health cadres found that 8 people were on the criteria of Good grades, and 2 people were Very Good. In conclusion, there was an increase in the value of health cadres' knowledge about exclusive breastfeeding after receiving health education by 26% and the skills of health cadres in providing counseling in the good category by 53%.